Cabinetware Employee Work System: Case Study at CV Diamond, Bandung, Indonesia - Nuzulan, Faza Firdaus; Shafira Putri, Adeela; Daniel Godjali, Vincentius; Archer, Raphael; Susanto, Sani; Yogasara, Thedy (Jurnal Improsci, 2025)
Background. The problems found in CV Diamond Cabinetware stem from the fact that all production activities for furniture and door handles are carried out using human labor, assisted by several machines. The factory's machines include bending, pounding, stamping, drilling, grinding, and hand shears. Aim. This study evaluates the current work system and designs ergonomic improvement solutions to reduce the risk of musculoskeletal disorders (MSDs). Data were collected through direct observation, semi-structured interviews, and workers completing the Nordic Body Map questionnaire. Methods. The risk analysis was carried out using the Rapid Entire Body Assessment (REBA) method, and the results showed a high level of ergonomic risk at specific workstations. Results. Based on the analysis results, improvements were made to ergonomic chairs and tables using SolidWorks software. Proposed improvements were evaluated through Human CAD simulations using CATIA V5 to assess the effectiveness of the design in reducing the risk of injury. Conclusion. The study's results show that the proposed ergonomic design has improved work posture, reduced physical stress, and improved employee comfort. Implementation. This study makes an essential contribution to the application of ergonomics in small-medium industries and is expected to be a reference for developing healthier and more productive work systems.